eCM 2019
DOI: 10.22203/ecm.v038a16
|View full text |Cite
|
Sign up to set email alerts
|

Vibration treatment modulates macrophage polarisation and enhances early inflammatory response in oestrogen-deficient osteoporotic-fracture healing

Abstract: Fracture healing is a well-orchestrated and coordinated process and begins with the inflammatory stage involving the infiltration of immune cells and the release of cytokines, including tumour necrosis factor-alpha (TNF-α), interleukin-6 (IL-6) and interleukin-10 (IL-10). Low-magnitude high-frequency vibration (LMHFV) stimulation is effective in promoting fracture healing. The study hypothesis was that the innate immune response was impaired in osteoporotic fracture and LMHFV could positively modulate it. 9-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 38 publications
3
49
0
Order By: Relevance
“…Chow et al investigated whether LMHFV influences the early inflammatory response after fracture in osteoporotic rats, because in estrogen-deficient, osteoporotic animal models, the innate immune response after fracture was shown to be altered (Chow et al, 2019). However, there is no clear consensus on whether the inflammation is lower (Chow et al, 2019) or rather increased (Haffner-Luntzer et al, 2017;Fischer et al, 2018). Chow et al (2019) found that LMHFV induced a phenotype switch from pro-inflammatory M1 to pro-regenerative M2 macrophages.…”
Section: Influence Of Lmhfv During the Early Inflammatory Phase Aftermentioning
confidence: 99%
See 1 more Smart Citation
“…Chow et al investigated whether LMHFV influences the early inflammatory response after fracture in osteoporotic rats, because in estrogen-deficient, osteoporotic animal models, the innate immune response after fracture was shown to be altered (Chow et al, 2019). However, there is no clear consensus on whether the inflammation is lower (Chow et al, 2019) or rather increased (Haffner-Luntzer et al, 2017;Fischer et al, 2018). Chow et al (2019) found that LMHFV induced a phenotype switch from pro-inflammatory M1 to pro-regenerative M2 macrophages.…”
Section: Influence Of Lmhfv During the Early Inflammatory Phase Aftermentioning
confidence: 99%
“…However, there is no clear consensus on whether the inflammation is lower (Chow et al, 2019) or rather increased (Haffner-Luntzer et al, 2017;Fischer et al, 2018). Chow et al (2019) found that LMHFV induced a phenotype switch from pro-inflammatory M1 to pro-regenerative M2 macrophages. M2 macrophages were previously demonstrated to promote osteogenic differentiation of progenitor cells (Zhang et al, 2017); therefore, this could represent a mechanism by which LMHFV might influence the fracture healing outcome.…”
Section: Influence Of Lmhfv During the Early Inflammatory Phase Aftermentioning
confidence: 99%
“…Chow et al 38 revealed that TNF-α level at the fracture callus by immunohistochemistry (IHC) was significantly lower compared to SHAM rats at week 1 post-fracture, while the serum level of TNF-α by enzyme-linked immunosorbent assay (ELISA) test was significantly higher in OVX rats at weeks 1 and 2. 38 Wang F et al 39 showed that the serum level of TNF-α by ELISA test was significantly higher in OVX mice at day 5 compared to SHAM mice but no significant difference was found at day 3 post-fracture. The level of TNF-α in serum by ELISA test was also found to be significantly higher in OVX rats at week 5 and week 6 by Zhang et al 40 and Wang J et al, 41 respectively.…”
Section: Inflammatory Factorsmentioning
confidence: 99%
“…Four out of seven preclinical studies included the proinflammatory cytokine IL-6, which stimulates angiogenesis 42 and MSCs to differentiate towards the osteoblast lineage 43 and modulates osteoblast and osteoclast activities. 44 Chow et al 38 demonstrated that IL-6 level at the fracture callus by IHC was significantly lower in OVX rats compared to SHAM rats at week 1 post-fracture. Significantly lower serum level of IL-6 was detected by ELISA test in OVX rats at week 8.…”
Section: Inflammatory Factorsmentioning
confidence: 99%
See 1 more Smart Citation